JUMLAH INDIVIDU DAN KELOMPOK BEKANTAN (Nasalis larvatus, Wurmb) Di TAMAN NASIONAL DANAU SENTARUM KABUPATEN KAPUAS HULU - Setiono, Sutejo Budi; Said, Syafruddin; anto, Eri (JURNAL HUTAN LESTARI, 2014)
Proboscis(Nasalis larvatus, Wurmb) including types that are rare andonly found in certain islands, especially on the island of Borneo and is a species endemic to the island. Leboyan Riverand Batang Ketam in one area of â€‹â€‹the National Park Lake Sentarum as a habitat of proboscis. This study aims to determine the number of individuals and groups of proboscis monkeys (Nasalis larvatus, Wurmb) Leboyan River and Batang Ketam in the National Park area of Lake Sentarum Kapuas Hulu District after the occurrence of forest fires in the region. The results of the data analysis of individual density proboscis at the 95% confidence interval is between 0,259 to 2,641 fish/ha, for a 99% confidence interval is between 0,313 to 3,213 fish/ha. The density of the groups with 95% confidence interval lies between 0.079 to 0.319 groups/ha and 99% confidence interval density lies between 0,021 proboscis groups to 0.377 groups/ha. The number of individuals in the study area throughout the proboscis monkey Leboyan River and Batang Ketam in the area Sentarum Lake National Park, at the 95% confidence interval is between 4 to 36 proboscis monkeys, for a 99% confidence lies between 5 and 43 proboscis monkeys. The number of groups of proboscis monkey with a 95% confidence interval is between 2 to 5 of proboscis monkeys and the 99% confidence interval is between 1 to 6 of proboscis monkeys. Keywords : Individual, Groups, Proboscis Monkeys, National Park Lake Sentarum. Â